Reconfiguration of knowledge: Academic experience of university reforms at the UTP 1980-1994 (2023)
Objective: Explore the change experienced in Colombian higher education since the eighties, specifically through analyzing the practical application of Decree Law 80/1980 at regional and local levels. The main objective is to fill a gap in existing knowledge about the impact of this decree on educational institutions, highlighting its influence on university daily life. Originality or Contribution: It focuses on a little-explored aspect of university reform in Colombia, focusing on the regional and local experience of the Universidad Tecnológica de Pereira. The aim is to provide a complete perspective on institutional development and the effects on the different university strata, thus contributing to the existing knowledge on the reforms of the eighties and nineties. Method: The research method is historical and is based on the analysis and contrast of primary sources, using the institutional archives of the Universidad Tecnológica de Pereira. Documents from the Higher and Academic Councils and testimonies from teachers and administrative staff were also analyzed. This approach allows institutional development to be contrasted with the experience of the different levels regarding the changes introduced by Decree Law 80/1980. Information Collection Strategy: Information collection strategies focus on detailed analysis of institutional documents and testimonials. The aim was to obtain a complete perspective on the implementation of the reforms, the Universidad Tecnológica de Pereira works here as a representative case study of the regional university experience during the period studied. Conclusions: The conclusions offer an opportunity to reflect on how the university reforms of the eighties and nineties, framed by Decree-Law 80/1980, gave a neoliberal character to everyday university life. The impacts on management, faculty, and student life are emphasized, using the UTP experience as a prism for understanding these changes in higher education.